A Multicenter Study of the Prevalence of Nasopharyngeal Carriage of Streptococcus pneumoniae in Selected Areas of the Republic of Kazakhstan Before and After the Onset of Antipneumococcal Vaccination - B. A. Ramazanova; L. T. Eralieva; K. K. Mustafina; E. A. Koloskova (Антибиотики и Химиотерапия)
Introduction. Colonization of S.pneumoniae is considered as a factor in the spreading of pneumococcus in the population, and is a predictor of the development of pneumococcal infection. Vaccination against pneumococcal infection can significantly reduce the spread of S.pneumoniae and the number of carriers of invasive strains. The vaccination against pneumococcal infection in the Republic of Kazakhstan was carried out with a phased coverage throughout the country in the framework of the national program «Salamatty Kazakhstan» in 2011. Purpose. To characterize the nasopharyngeal carriage of S.pneumoniae in children under 2 years in two different regions of the country with different histories of immunization against pneumococcal infection. Methods. A prospective multicenter cross-sectional study was conducted in two cities - Almaty and Karaganda - for a two-year period. Nasopharyngeal samples were identified by microbiological and molecular/genetic methods, taking into account the vaccinal status of children. Results: During the study, 500 children from Almaty and 1000 children from Karaganda at the age of 2 years were examined. The prevalence of pneumococcal carriage in the first stage of the study was 15.6% in Almaty and 4.7% in Karaganda. In the second year of the study, the prevalence of pneumococcal carriage was 14.1% in Almaty and 17.6% in Karaganda. The most common serotypes in Almaty before the vaccination were: 13 - 12%, 6ABC - 8%, 15B/C - 8% and 17F - 8%, in Karaganda, where the vaccination was carried out for 2 years: 15V - 19%, 31 - 14, 3%, 38 - 14.3% and non-typed strains - 23.8%. At the second stage of the study, common serotypes in Almaty were: 15A - 11.1%, 39F - 11.1%, 22F - 8.3%, 31 - 8.3% and non-typed strains - 27.8%. The most frequently detected serotypes in Karaganda in 2016 were: 8 - 14.3%, 10F/10C/33C - 10.4%, 15B/C - 9.1% and non-typed strains - 23.4%. Discussion. The received data confirms the necessity of the monitoring measures within the framework of the current anti-pneumococcal vaccination.